Meningeal lymphatics and their role in CNS disorder treatment: moving past misconceptions - Melloni, Alexandra; Liu, Longsha; Kashinath, Vivek; Abdi, Reza; Shah, Khalid (Frontiers in Neuroscience, 2023)
The central nervous system (CNS) was previously thought to lack lymphatics and shielded from the free diffusion of molecular and cellular components by the blood-brain barrier (BBB) and the blood–cerebrospinal fluid barrier (BCB). However, recent findings have redefined the roles played by meningeal lymphatic vessels in the recruitment and drainage of lymphocytes from the periphery into the brain and potentiation of an immune response. Emerging knowledge surrounding this importance of meningeal lymphatics has the potential to transform the treatment of CNS disorders. This review details the most recent understandings of the CNS-lymphatic network and their immunological implications in both the healthy and diseased brain. Moreover, the review provides an in-depth coverage of several exciting avenues for future therapeutic treatments that involve the meningeal lymphatic system. These therapeutic avenues will have potential implications in many treatment paradigms in coming years.